2015
DOI: 10.4238/2015.april.13.16
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the migratory inhibitory factor, IL-17, and IL-10 levels in serum from chronic hepatitis B patients and clinical significance following Baraclude® treatment

Abstract: ABSTRACT. This study aimed to determine the relationship between changes in the serum levels of macrophage migratory inhibitory factor (MIF), interleukin (IL) 17, and IL-10 during chronic hepatitis B treatment via Baraclude ® (Bristol-Meyers Squibb). Thirty-six patients with chronic hepatitis B and 24 healthy individuals were selected as the experimental and control groups, respectively, and the serum levels of MIF, IL-17, and IL-10 were measured during the period in which the experimental group was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…IL-23, a member of the IL-12 cytokine family, is necessary for the survival and population expansion of Th17 cells [ 12 ] and responsible for inflammatory disorders through its downstream Th17 pathway [ 13 , 14 ]. Studies by Yu et al [ 15 ] have revealed that, in the hepatitis B virus (HBV) patients receiving antiviral therapy with Baraclude, there was a gradual decrease in the serum level of IL-17. Decreased HBV load was associated with decreased frequency of Treg cells, reduced level of IL-23, partially restored T cell immune response, and significant improvement of liver inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-23, a member of the IL-12 cytokine family, is necessary for the survival and population expansion of Th17 cells [ 12 ] and responsible for inflammatory disorders through its downstream Th17 pathway [ 13 , 14 ]. Studies by Yu et al [ 15 ] have revealed that, in the hepatitis B virus (HBV) patients receiving antiviral therapy with Baraclude, there was a gradual decrease in the serum level of IL-17. Decreased HBV load was associated with decreased frequency of Treg cells, reduced level of IL-23, partially restored T cell immune response, and significant improvement of liver inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…37 , 38 It is also believed that the elevated serum level of IL-10 may be partly responsible for the poor clinical outcome of antiviral treatment. 39 Because IL-10 is a powerful immune and inflammatory inhibitory factor, it not only inhibits Th1 cellular immune response but also inhibits cytokines secreted from Th1 cells. 40 , 41 IL-10 could act on the early stage of dendritic cell maturation, inhibit the expression of costimulatory molecules, as well as reduce the expression of major histocompatibility antigen class II molecules, leading to the suppression of the maturation and differentiation of dendritic cells.…”
Section: Discussionmentioning
confidence: 99%